2017
DOI: 10.11591/edulearn.v11i1.4301
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perspectives on Speaking Anxiety in the English Foreign Language Classroom

Abstract: Anxious students are often concerned about the impressions that others form of them. When such students are confronted in a classroom with a learning situation that makes them uncomfortable, they may choose to withdraw from the activity. Some learners believe they cannot perform in English and consequently form negative expectations, which in turn lead to decreased effort and the avoidance of opportunities to enhance their communication skills. The goal of this study was to identify those factors, as perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…The eighteenth question, which elicited an agreed response there was 47.5%, because the third semester student of English education always thought that the other student was better at speaking English than himself. It is in line with previous study that state analyse the relationships between foreign language speaking anxiety and demographic factors among undergraduate students (Enisa & Karairmak, 2017). The findings revealed that foreign language speaking anxiety was negatively correlated with two variables related to prior foreign language experience as well as having a foreign friend.…”
Section: Discussionsupporting
confidence: 91%
“…The eighteenth question, which elicited an agreed response there was 47.5%, because the third semester student of English education always thought that the other student was better at speaking English than himself. It is in line with previous study that state analyse the relationships between foreign language speaking anxiety and demographic factors among undergraduate students (Enisa & Karairmak, 2017). The findings revealed that foreign language speaking anxiety was negatively correlated with two variables related to prior foreign language experience as well as having a foreign friend.…”
Section: Discussionsupporting
confidence: 91%
“…Raja (2017) also suggested that strategies such as practicing and rehearsing before the actual performance help alleviate the fear of speaking in public. Similarly, Khusnia (2017) noted that practicing before performing helps in coping up with speaking anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Causal factors of distress are not the only approach to exploring FLA, finding the remedies or interventions would also aid learners to reduce their apprehension. Similarly, numerous academics are able to come up with several intervention strategies in a view to support learners to overcome their fear of foreign languages (Enisa & Karairmak, 2017;Tsiplakides & Keramida, 2009). A limited number of scholars considered studying foreign language anxiety across disciplines, specifically in the Malaysian setting.…”
Section: Background Of Studymentioning
confidence: 99%